ANALISIS TREN PUBLIKASI DAN HUBUNGAN ANTARA UKURAN PERUSAHAAN DENGAN NILAI PERUSAHAAN: PENDEKATAN BIBLIOMETRIK - Dermawan, Wildan Dwi; Pradani, Tiara (Universitas Sarjanawiyata Tamansiswa, 2025)
The aim of this study is to explore publication trends and the relationship between firm size and firm value and provide recommendations for researchers. The database used is dimensions.ai from 1990 - 2024. The data collected were 482 documents using the keywords